New development in public administration: country report: citizen's charter: people's charter in the UK - Duggett, Michael (1998)
Dealing with change within the change process itself - this has become one of the essential policy skills for all modern public servants. The United Kingdom Citizen's Charter was launched by one prime minister and it is being continued, if modified, by another. It was one of the flagship policies of one regime, which did not achieve re-election, but it is still a relatively prominent policy of the Government that replaced it in May 1997. Now carrying a new title, in part, it remains of interest as an example of central government's desire to bring home the need for change not only to its own direct staff, but to those over whom it has more influence than control. - Reproduced
Keywords: Public administration - Great Britain; Public administration